Interstitial Cells of Cajal and Intestinal Function in Trinidadian Children - ANATOL, T; MOHAMMED, W; RAO, C (West Indian medical journal, 2008)
This study was carried out to compare the density of the interstitial cells of Cajal (ICCs) in the bowel wall of children with Hirschsprung's disease (HD), anorectal malformations (ARM) and normal controls in Trinidad and Tobago. Segments of bowel wall excised from eight children with HD, three controls and two children with ARM were immunostained with c-Kit primary antibody. Cells with features of ICCs were counted. All three controls and the two children with ARM had dense distribution of ICCs. Most children (6/8; 75%) with HD had markedly reduced counts in aganglionic bowel. Two (25%) also had a decrease in ganglionic bowel. Possible influences were patient age and gender and the level of bowel sectioned. Analysis of this sample suggests that immunostaining for c-Kit positive cells might be a useful screening test in the assessment of bowel motility disorders. The possible effects of age, gender and the level of bowel sampled await determination.